2017
DOI: 10.1038/s41598-017-09775-0
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic radiotherapy (TRT) improved survival in both oligo- and polymetastatic extensive stage small cell lung cancer

Abstract: There has been no previous study on the efficacy of the thoracic radiotherapy (TRT) in oligometastatic or polymetastatic extensive stage small-cell lung cancer (ES-SCLC) to the overall survival (OS). In a group of 270 ES-SCLC cases retrospective study, 78 patients (28.9%) had oligometastases and 192 (71.1%) had polymetastases, among which 51 oligometastatic patients (65.4%) and 93 polymetastatic patients (51.6%) received TRT. Propensity score matching (PSM) was utilized. The 2-year OS, progression free surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 36 publications
6
35
1
Order By: Relevance
“…More recent clinical studies have demonstrated that consolidative TRT in addition to platinum-based chemotherapy improved the 2-year OS from 13% to 38%. 5 12 The current study also showed that consolidative RT in addition to chemotherapy improved the median OS for all metastatic SCLC from 7.0 to 9.0 months ( P <0.001). We observed the best OS in patients with only lung metastasis who, presumably, had also received TRT, with a median OS of 12.0 months.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…More recent clinical studies have demonstrated that consolidative TRT in addition to platinum-based chemotherapy improved the 2-year OS from 13% to 38%. 5 12 The current study also showed that consolidative RT in addition to chemotherapy improved the median OS for all metastatic SCLC from 7.0 to 9.0 months ( P <0.001). We observed the best OS in patients with only lung metastasis who, presumably, had also received TRT, with a median OS of 12.0 months.…”
Section: Discussionsupporting
confidence: 60%
“…Given the radiosensitive nature of SCLC, RT has been used to control locoregional and/or metastatic disease to improve overall survival (OS) by Jeremic et al and others over the past two decades. 5 12 However, controversy remains regarding the role of consolidative RT in ED-SCLC because of scant prospective randomized controlled trial (RCT) data. Although a recent Phase II study did not find a survival benefit at 1 year when thoracic radiotherapy (TRT) was added to induction chemotherapy for patients with stage IV disease, 13 two Phase III prospective RCTs observed an improved OS for ED-SCLC patients who responded to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…For metastatic cervical cancer, local control of the primary tumor could reduce the symptoms, intrapelvic disease burden, and gastrointestinal/genitourinary compression, all of which could be associated with better OS. 8,16 The control of extensive metastatic nonYsmall cell lung cancer 17Y20 and extensive metastatic small cell lung cancer 21,22 have been found related to a better survival. Similarly, we expect that controlling both primary tumor and metastatic tumor might also prolong the survival for patients with extensive metastatic cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The prescription dose was 30-60 Gy in fractions of 1.8-3 Gy. 13 Doses in organs at risk were generally within normal limits; 9 patients received concurrent chemotherapy during thoracic radiotherapy.…”
Section: Treatmentmentioning
confidence: 99%